Prevalence of exposure to occupational carcinogens among farmers. - Darcey, E.; Carey, Renee; Reid, Alison; Driscoll, T.; Glass, D.; Benke, G.; Peters, S.; Fritschi, Lin (Deakin University, 2018)
INTRODUCTION: Farmers experience a range of carcinogenic exposures, including some pesticides, fuels, engine exhausts, metals, some organic solvents, silica, wood dusts and solar radiation. However many studies investigating the risk of cancer in farmers focus on pesticide exposure alone. The aim of this study was to determine which carcinogens Australian farmers are exposed to, the prevalence and circumstances of those exposures, and the use of protective equipment. METHODS: The study used data from the Australian Work Exposures Study (AWES) a cross-sectional study conducted in 2012 that investigated the prevalence of carcinogen exposure among Australian workers. This was supplemented with data from AWES-Western Australia (WA), conducted in 2013, which followed the same methodology but in Western Australian workers only. A total of 5498 Australian workers were interviewed about the tasks they carry out in their workplace. The 166 participants who worked in farming (126 men and 40 women, with an age range of 18-65 years) are the focus of this article. RESULTS: On average, farmers had been exposed to five different carcinogens. Highest numbers of exposures occurred among men and those working on mixed crop and livestock farms. Solar radiation, diesel engine exhaust and certain solvents were the most prevalent exposures, each with over 85% of farmers exposed. The main tasks leading to exposure were working outdoors, using and repairing farming equipment and burning waste. Sun protection and closed cabs on machinery were the most frequently used forms of protection. CONCLUSIONS: Farmers are a high risk group in relation to carcinogen exposure. The variation in tasks that they undertake results in exposure to a wide variety of different carcinogens that require similarly varied control measures.